The Potential of Sea Worm Perinereis aibuhitensis Extract as Anti-microbe toward Bacteria Salmonella typhi and Fungus Candida albicans - Andi Evi Erviani; Asadi Abdullah; Nurwahida Nurwahida; Febriany Tairas (Hasanuddin University, 2019)
The research about the potential of sea worm Perinereis aibuhitensis extract as anti-microbe toward bacteria Salmonella typhi and fungus Candida albicans had been conducted. The aim this research is to know the extract’s concentration of sea worm Perinereis aibuhitensis which is effective to obstruct the growth of bacteria Salmonella typhi and fungus Candida albicans. The result of research that was obtained shows that sea worm’s extract which used ethanol solution 96% and was needed in the culture of bacteria Salmonella typhi with the concentration of sea worm’s extract 7.5%, 15%, 30%, and 60% involved the form of obstruction zone at the medium with duration incubation 1x24 hours and 2x24 hours. Based on the research which was conducted, it can be concluded that the sea worm Perinereis aibuhitensis extract had the potential as anti-microbe toward bacteria Salmonella typhi because can obstruct the growth of that bacteria, but it had no effect as anti-microbe toward fungus Candida albicans.